Blanco’s London, 1810-1832 - Murphy, Martin (Cuadernos de Ilustración y Romanticismo, 2025)
The Spanish journalist and writer José María Blanco y Crespo went into exile in London in 1811 and from then on, under the name Joseph Blanco White, he developed his life and work there. This study presents the main features of the relationship between the writer and London up to the time he left the city.